Identificación de agentes etiológicos en infecciones de vías urinarias de pacientes embarazadas que acuden al Centro de Salud Universitario de Motupe - Arévalo Abad, Erika Anabel (2023)
Urinary tract infections (UTI) are common in pregnant patients due to physiological, anatomical, and hormonal changes that make them more susceptible, since it favors the imbalance of the microbiota and thus facilitates the colonization of bacteria, which manifest as asymptomatic bacteriuria, cystitis, or pyelonephritis. The present study aimed to identify the etiological agents in urinary tract infections in pregnant patients attending the University Health Center of Motupe in the period October 2022 - March 2023, using a non-experimental quantitative approach, with a descriptive cross-sectional design. Of 85 samples analyzed by general urine examination, 67 were determined to meet the inclusion criteria, of which 7 were categorized as pathological, and were subjected to specific methods corresponding to sowing in blood agar, MacConkey and eosin methylene blue (EMB) culture media, which in turn allowed following the algorithm for identifying etiological agents according to the characteristics they presented; for gram-positive bacteria, catalase, coagulase, bacitracin and novobiocin tests were used on Mueller-Hinton agar, while for gram-negative bacteria, biochemical tests of citrate, lysine, indole sulfide for motility (SIM), urea and triple sugar iron (TSI) were used, urea and triple sugar iron (TSI), with which it was possible to identify that the most prevalent etiological agents belong to the Enterobacteriaceae family and the Staphylococcus genus, with Escherichia coli responsible for 86% of the infections and Staphylococcus saprophyticus for 14%. Therefore, these results contribute significantly to the importance of early detection and treatment of UTIs during pregnancy in order to prevent complications that increase maternal and fetal morbidity and mortality